Letní etologické školy na Fakultě humanitních studií Univerzity Karlovy - Redakce (Lidé města, 2007)
During the past five years, the Faculty of Humanities of the Charles University have held summer ethologic schools focusing on ethology of human beings. The lectures were organized in separate blocks and each lecturer introduced his own area of research. Students thus had an exceptional opportunity to hear in English the latest finding in the area of human ethology and could also meet and discuss personally with leading scientists of this field. During the period we organized these summer schools, our department has been visited (among others) by the following personalities: Prof. Zoya Zorina, Moscow State University, Russia, Dr. Kim Bard, Portsmouth University, U.K., Prof. Ludwig Huber, Vienna University, Austria, Dr. Frank Salter, Laboratory of Human ethology, Max-Plank Institute, Adechs, Germany, Zhanna Reznikova, Dept. of Comparative Psychology of Novosibirsk State University; Laboratory of Community Ethology, Institute for Animal Systematics and Ecology, Siberian Branch RAS, Russia Dr. Zsofia Viranyi, Dept. of Ethology, Eötvös University, Budapest, Hungary, and Konrad Lorenz Institute for Evolution and Cognition Research, Altenberg, Austria, Dr. Christian Lehmann, Adechs, Germany, Dr. Kirsty Brown, Portsmouth University, U.K. We are presenting two of the lectures that have been presented at our department, during the period these schools were organized and held, in the issue of Urban People revue.